Pemberdayaan Kelompok Pengrajin Sopi dalam Diversifikasi untuk Penyangga Ekonomi di Kelurahan Naimata, Kota Kupang - Aurelia Febriyanti Siti; Margareta Lidia Gunu; Yosefa Maria Robio Gulok; Yohanes P Lian (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study analyzes the empowerment strategy for traditional Sopi liquor artisan groups in Naimata Village, Kupang City, through a product diversification program aimed at strengthening the local economy. Sopi, produced from tapping lontar palm sap, has high cultural and economic value in East Nusa Tenggara (NTT). However, this potential still faces several major obstacles, including unclear legality, low quality standardization, and limited development of processed lontar-derived products. This research uses a descriptive qualitative method with a Participatory Rural Appraisal (PRA) approach to explore community conditions, needs, and empowerment opportunities. The findings show that diversification can be developed through non-alcoholic products, such as sap vinegar, lontar palm sugar, and sap syrup, as well as the standardization of alcoholic products in the form of Premium Sopi. The diversification program increased average total family income by 50.0%, from IDR 1,200,000 to IDR 1,800,000 per month. Therefore, this program not only expands income sources but also encourages community economic transformation based on local potential and regional cultural wisdom in an inclusive and sustainable manner.